Composition and role of hoverfly (Diptera: Syrphidae) communities in an organic apple orchard - Földesi, Rita; Medgyessy, István (Acta Agraria Debreceniensis, 2009)
The use of hoverfly (Syrphidae) larvae in biological control is gaining more attention where the damage by their prey, aphids is significant, especially in agricultural fields and orchards, where they lower the number of aphids. The present study focuses on one hand on faunistics, on the other hand on testing the different available collecting methods for later research. Collecting in an organic apple orchard near Debrecen yielded 525 specimens of Syrphidae mostly by netting but also with white tray traps. Collected species are differentiated according to their feeding (94.1% aphidophagous). The three species found in greatest numbers are Sphaerophoria scripta (Linnaeus, 1758), Melanostoma mellinum (Linnaeus, 1758) and Episyrphus balteatus (De Geer, 1776). The available information on their biology is reviewed and their potential value of hoverflies in biological control is discussed.